Building Learning Awareness: Mindful Learning Strategies in the Independent Curriculum in Balinese Culture-Based Schools - Karmini, Ni Wayan; Bagus Purwasidemen, Ida; Wahyu Adi Gotama, Ni Nyoman; Yudabakti, Imade; Sri Winarti, Ni Nyoman (Yayasan Pendidikan Islam Daarut Thufulah, 2025)
Background. Learning awareness is an important element in the modern education system, especially in the implementation of the Independent Curriculum which emphasizes the flexibility and independence of students. Mindful learning is present as a strategy that can help students manage attention, improve focus, and understand the material more deeply. Balinese culture-based schools have great potential in implementing mindful learning because of the values of local wisdom that are in line with the principles of mindfulness. Purpose. This study aims to analyze the effectiveness of mindful learning strategies in increasing learning awareness in Balinese culture-based schools in the context of the Independent Curriculum. The study also explores how the integration of local cultural values can strengthen the implementation of mindful learning in the education system. Method. This study uses a mixed-method method with a quasi-experimental design and a case study. The research sample consisted of several Balinese culture-based schools, namely SMA Negeri 1 Ubud, SMA Saraswati Denpasar, and SMA Negeri 2 Singaraja. Quantitative data was collected through mindful learning scale instruments and classroom observation, while qualitative data was obtained from teacher interviews and student reflections. Results. The results showed that mindful learning applied with a culture-based approach increased students' learning awareness by up to 21.5%, with the greatest impact on emotional regulation and engagement in learning. The most effective approaches to mindful learning are awareness-based discussions, daily reflection journals, and learning based on local wisdom. Conclusion. Mindful learning integrated with local culture has proven effective in increasing students' learning awareness. The integration of Balinese cultural values strengthens the relevance and depth of mindfulness practices in the context of Merdeka Curriculum education.